Clinical application of fully digital self-glazed ultra-thin zirconia veneers. (17th November 2021) - Chen, Ding; Su, Zhikang; Pi, Yixing; Li, Fuyao; Liang, Tingting; Huang, Jiangyong; Luo, Tao; Guo, Lvhua
ABSTRACT : Monolithic self-glazed zirconia is a new type of biomimetic zirconia that has been successfully used as crown and bridge restorations in the anterior and posterior regions. It exhibits excellent biomechanics and aesthetic properties through completely digital processing technology. This case presents a young patient's aesthetic rehabilitation with self-glazed ultra-thin zirconia veneers by closing the scattered diastema in the aesthetic zone of the anterior teeth with a fully digital workflow. The restorations exhibited excellent aesthetic outcomes with a minimally invasive concept and superior mechanical properties over glass-based ceramic veneers. The application of full-contour monolithic ultra-thin self-glazed zirconia restorations in the anterior aesthetic zone constitutes a reliable, fully digital clinical workflow.